2006
DOI: 10.1002/ps.1274
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Portland cement amendment on soil pH and residual soil termiticide performance

Abstract: Soil adjacent to new brick veneer work is likely to have a higher pH owing to the mixture of cement with the soil. In the Gainesville, FL, area, soil samples taken from such locations had a range of pH values from 9.0 to 10.1; similar soils used in bioassays had a pH of 5.6 before the addition of cement. Addition of 15 mg of Portland cement to 33 g of soil increased the pH to 6, and addition of 291 mg of Portland cement increased the pH to 9. The pH of soil amended with cement was stable for the first 5 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Adsorption is directly influenced by soil organic matter acting as a sink whereby gradual availability of a termiticide is diminished by time. Richman et al (2006) found inverse relationship between soil pH and mortality in which increased pH diminished residual activity of termitcides.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Adsorption is directly influenced by soil organic matter acting as a sink whereby gradual availability of a termiticide is diminished by time. Richman et al (2006) found inverse relationship between soil pH and mortality in which increased pH diminished residual activity of termitcides.…”
Section: Discussionmentioning
confidence: 90%
“…Because soil conditions adjacent to structures where termiticide is applied accelerated dissipation and biological transport (by plants), both might factor in persistence of imidacloprid-treated soils (Scholz and Spiteller 1992, Rouchard et al 1994, Sarkar et al 2001, Richman et al 2006. Adsorption is directly influenced by soil organic matter acting as a sink whereby gradual availability of a termiticide is diminished by time.…”
Section: Discussionmentioning
confidence: 98%
“…According to the Powers [34][35][36][37] theory, as the hydration reaction proceeds, the volume fraction of hydration products increases, reducing the sample's pore volume. Increasing OH − ion concentration during cement hydration reaction will increase the pH value [38]. HA is soluble in dilute alkaline solution, partially dissolves HA particles during soaking, increasing pore volume [39].…”
Section: Mercury Intrusion Test Results and Analysismentioning
confidence: 99%
“…The pH of NCs is slightly below 7. This is acidic in nature, and thus, is not expected to raise the pH of UKM soil when compared to lime or cement is used for stabilization [31]. With a pH of 4.14, the soil is strongly acidic and can produce better dispersion of NCs due to the presence of hydrogen ions.…”
Section: Effect Of Soil Ph On Dispersion Nanocarbonmentioning
confidence: 99%